Method for preparing ammonia through microwave catalytic reduction of nitrate

By using a method of combining Pd-ZnFe2O4@C@MoS2 composite catalyst with microwave heating, the problems of complex process, high cost and high energy consumption of the catalytic reduction nitrate ammonia production method in the prior art are solved, and efficient and low-energy-consuming ammonia production is achieved, and the catalyst can be reused, reducing production costs.

CN119591125APending Publication Date: 2025-03-11WUHAN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411651260.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing catalytic reduction nitrate ammonia production methods have problems such as complex process, high cost, high energy consumption, many by-products, low energy utilization and difficulty in large-scale application.

Method used

Ammonia was prepared by combining Pd-ZnFe2O4@C@MoS2 composite catalyst with microwave heating. The method includes mixing the catalyst with a nitrate solution, adding a hole scavenger, adjusting the pH value, and then reacting in a microwave reaction device.

Benefits of technology

It realizes efficient production of ammonia, with high ammonia selectivity, high energy utilization, low energy consumption, and the catalyst is magnetically reusable, reducing production costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591125A_ABST
    Figure CN119591125A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ammonia production, and particularly relates to a method for producing ammonia through microwave catalytic reduction of nitrate. According to the technical scheme, the method comprises the following steps: adding a catalyst into a nitrate solution according to the mass ratio of the catalyst to the nitrate solution of (0.001-0.1): 1 to obtain a mixed solution; adding a hole scavenger accounting for 1-5wt% of the mass of the mixed solution into the mixed solution, adjusting the pH value of the solution to 1-6 with hydrochloric acid, and stirring in a darkroom for 1-2 hours to obtain a turbid liquid I; and then putting the turbid liquid into a microwave reaction device, and reacting for 30 to 240 minutes under the microwave irradiation condition of 0.3 to 20 GHz, so as to prepare ammonia. The method has the characteristics that the operation is simple, the cost is low, the energy consumption is low, the catalyst can be repeatedly used, and the large-scale production is easy. The method for preparing the ammonia through the microwave catalytic reduction of the nitrate is high in ammonia production efficiency and high in ammonia selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ammonia production, and specifically relates to a method for producing ammonia by microwave catalytic reduction of nitrate. Background Art

[0002] Ammonia (NH3) is one of the most important basic chemical compounds in modern industry. It is widely used in industry and agriculture, with an annual global demand of up to 150 million tons. The main method for producing ammonia is the Haber-Bosch process, which requires a high temperature of 500°C and a pressure of more than 100 atm, and causes 2% of global energy consumption and 1.6% of carbon dioxide emissions each year. The bond energy of the N=O bond in nitrate is much lower than the bond energy of the N≡N bond in nitrogen (204 kJ / mol vs 941 kJ / mol), and can be decomposed at a lower dissociation energy, which helps to accelerate the reaction kinetics of ammonia synthesis. Therefore, the reduction of nitrates to produce ammonia can reduce energy consumption and greenhouse gas emissions. In recent years, photocatalysis and electrocatalysis have been widely used to reduce nitrates to produce ammonia, but these methods still have many defects. For example:

[0003] The patented technology "Preparation method of porous carbon nitride-ferrite composite catalyst with double defect structure containing nitrogen / oxygen and application of photo-nitrogen fixation" (CN202111174873.0) provides a method for photocatalytic nitrogen fixation and ammonia production using porous carbon nitride-ferrite composite catalyst with double defect structure containing nitrogen / oxygen. Although this technology has the advantages of simple operation, energy saving and environmental protection; however, the catalytic process produces many by-products, the energy utilization rate of the catalyst is low, the equipment and raw materials used are expensive, and the cost is relatively high.

[0004] The patented technology "An in-situ grown copper-containing photocatalyst, preparation method and its application in nitrate reduction to synthesize ammonia" (CN202211256534.1) discloses a preparation method for an in-situ grown copper-containing titanium dioxide photocatalyst and a method for photocatalytic reduction of nitrate to synthesize ammonia. Although this technology can achieve efficient and green synthesis of ammonia under mild conditions of normal temperature and pressure; however, the reaction efficiency is low, and its photocatalytic synthesis of ammonia requires long-term xenon lamp irradiation, which has high energy consumption.

[0005] The patented technology of "water treatment method for controllable conversion of nitrate into ammonia or nitrogen on the same photocatalyst" (CN202310796397.9) provides a method for producing ammonia by photocatalytic controllable reduction of nitrate using bismuth oxybromide-bismuth tungstate catalyst. Although this technology can achieve selective regulation of the conversion of nitrate into ammonia; however, the ammonia produced by this method has low selectivity, many by-products, and insufficient light absorption capacity of the catalyst, resulting in low energy utilization.

[0006] The patented technology "A single-atom iron-doped 3D defect carbon nitride electrode and its preparation method and application" (CN202410171405.5) provides a preparation method of a single-atom iron-doped 3D defect carbon nitride electrode and its application in electrocatalytic reduction of nitrate in sewage to produce ammonia. Although this technology has a high nitrate degradation efficiency, the scale of the electrocatalytic reaction equipment is too small and the equipment cost is high, so it cannot be used on a large scale.

[0007] In summary, the existing method of producing ammonia by catalytic reduction of nitrate has the problems of complex process, high cost, high energy consumption, many by-products, low energy utilization rate and difficulty in large-scale application. Summary of the invention

[0008] The present invention aims to overcome the deficiencies in the prior art and aims to provide a method for preparing ammonia by microwave catalytic reduction of nitrates, which is simple to operate, low in cost, low in energy consumption, easy to mass produce, and has a reusable catalyst. The method has high ammonia production efficiency and high ammonia selectivity.

[0009] To achieve the above object, the technical solution of the present invention is:

[0010] According to the mass ratio of catalyst to nitrate solution of 0.001 to 0.1:1, the catalyst is added to the nitrate solution to obtain a mixed solution; then a hole scavenger accounting for 1 to 5 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 1 to 6 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1 to 2 hours to obtain a suspension I; then the suspension is placed in a microwave reaction device, and reacted for 30 to 240 minutes under microwave irradiation conditions of 0.3 to 20 GHz to obtain ammonia.

[0011] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0012] Step 1: Preparation of ZnFe2O4@C fiber mat

[0013] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of ZnFe2O4 powder: polyacrylonitrile: N,N-dimethylformamide of 1:2.4-4:13-15 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 60-80°C and a rotation speed of 800-1000 r / min to obtain an electrospinning solution.

[0014] The electrospinning solution is injected into the syringe of the electrospinning device, and the spinning is carried out for 6 to 8 hours under the conditions of an applied voltage of 12 to 16 kV, an injection speed of 40 to 80 μL / min, and a distance between the spinning syringe needle and the collector of 15 to 20 cm to obtain a ZnFe2O4@C precursor.

[0015] The ZnFe2O4@C precursor is placed in an oven and dried at 200-240°C for 4-6 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0016] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0017] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed according to the mass ratio of the ZnFe2O4@C fiber felt: Na2MoO4·2H2O: thiourea: deionized water of 1:2-4:2.5-3.5:18-30, and stirred for the second time to obtain a suspension III.

[0018] The suspension III is placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor is placed in a hydrothermal oven, heated to 200-240°C, kept warm for 10-14 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0019] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0020] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1: 0.4-0.6: 0.01-0.02: 450-540: 50-60, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0021] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 90-100°C, kept warm for 20-40 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0022] The nitrate solution is domestic wastewater, industrial wastewater, agricultural wastewater containing nitrate or an aqueous solution prepared using nitrate; the nitrate concentration in the nitrate solution is 0.001-1 g / L.

[0023] The first stirring time is 48 to 60 hours.

[0024] The carbonization treatment is to heat to 390-400°C at a heating rate of 0.5-1°C / min under N2 atmosphere, keep warm for 110-120min, and then heat to 590-600°C at a heating rate of 4.5-5.5°C / min, and keep warm for 110-120min.

[0025] The second stirring time is 10 to 30 minutes.

[0026] The temperature of the second drying is 60-80° C., and the time is 30-60 min. The conditions of the third drying and the fourth drying are the same as those of the second drying.

[0027] The hole scavenger is one of formic acid, ethylene glycol, oxalic acid, isopropanol or ascorbic acid.

[0028] The microwave reaction device is one of a household microwave oven, an industrial microwave oven or a laboratory microwave reactor.

[0029] Due to the adoption of the above technical solution, the present invention has the following positive effects and outstanding features compared with the prior art:

[0030] 1. The catalyst raw materials used in the present invention have a wide range of sources. Although the precious metal palladium is required in the catalyst raw materials, the loading amount of palladium metal Pd in ​​the catalyst is only 1wt%, and the production cost can still be kept low even if the catalyst is prepared on a large scale. In addition, the catalyst has magnetic properties and can be quickly separated and recovered from the solution by simple magnetic separation. The catalyst has high reusability, so the production cost and energy consumption can be reduced.

[0031] 2. The microwave heating method used in the present invention has the characteristics of strong penetration, uniform heating and selective heating. Compared with photocatalysis and electrocatalysis, the unique selective heating of the catalyst by microwaves can ensure that the microwave energy is efficiently used by the catalyst for the catalytic reduction reaction of nitrates, with high energy utilization and low energy consumption, which can significantly reduce production costs.

[0032] 3. The microwave catalytic method used in the present invention utilizes a large number of "hot electrons" excited by the unique "hot spot effect" of microwave irradiation to reduce nitrates. The "hot spot effect" is a high-temperature microscopic quantum dot generated by molecular friction and vibration of the catalyst under microwave irradiation, which can excite "hot electrons" with high energy and catalytic activity. The reaction rate of reducing nitrates to produce ammonia is high, so the ammonia production efficiency is high and the ammonia selectivity is high. NO3 produced from ammonia- The conversion rate is 35.61-99.11%, NH4 + The selectivity is 28.22~93.92%.

[0033] 4. The microwave catalytic method adopted in the present invention only requires mixing the catalyst with the nitrate solution and placing it under microwave irradiation to complete the microwave catalytic reduction reaction of nitrate. The process is simple and the operation is convenient; and currently there is industrial microwave reaction equipment that can support large-scale production.

[0034] Therefore, the present invention has the characteristics of simple operation, low cost, low energy consumption, reusable catalyst and easy large-scale production. The method for preparing ammonia by microwave catalytic reduction of nitrate has high ammonia production efficiency and high ammonia selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is an X-ray diffraction pattern of a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst prepared by the present invention;

[0036] Figure 2 for Figure 1 The scanning electron microscope image of the Pd-ZnFe2O4@C@MoS2 composite microwave catalyst is shown;

[0037] Figure 3 for Figure 1 Transmission electron microscopy image of the Pd-ZnFe2O4@C@MoS2 composite microwave catalyst shown;

[0038] Figure 4 for Figure 1 The Pd-ZnFe2O4@C@MoS2 composite microwave catalyst was used to treat 100 mg / L nitrate solution with NO3 - Concentration and NH4 + Concentration versus reaction time. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with specific implementation modes. Those skilled in the art should understand that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0040] A method for producing ammonia by microwave catalytic reduction of nitrates. The method for producing ammonia in this specific embodiment is:

[0041] According to the mass ratio of catalyst to nitrate solution of 0.001 to 0.1:1, the catalyst is added to the nitrate solution to obtain a mixed solution; then a hole scavenger accounting for 1 to 5 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 1 to 6 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1 to 2 hours to obtain a suspension I; then the suspension is placed in a microwave reaction device, and reacted for 30 to 240 minutes under microwave irradiation conditions of 0.3 to 20 GHz to obtain ammonia.

[0042] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0043] Step 1: Preparation of ZnFe2O4@C fiber mat

[0044] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of ZnFe2O4 powder: polyacrylonitrile: N,N-dimethylformamide of 1:2.4-4:13-15 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 60-80°C and a rotation speed of 800-1000 r / min to obtain an electrospinning solution.

[0045] The electrospinning solution is injected into the syringe of the electrospinning device, and the spinning is carried out for 6 to 8 hours under the conditions of an applied voltage of 12 to 16 kV, an injection speed of 40 to 80 μL / min, and a distance between the spinning syringe needle and the collector of 15 to 20 cm to obtain a ZnFe2O4@C precursor.

[0046] The ZnFe2O4@C precursor is placed in an oven and dried at 200-240°C for 4-6 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0047] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0048] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed according to the mass ratio of the ZnFe2O4@C fiber felt: Na2MoO4·2H2O: thiourea: deionized water of 1:2-4:2.5-3.5:18-30, and stirred for the second time to obtain a suspension III.

[0049] The suspension III is placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor is placed in a hydrothermal oven, heated to 200-240°C, kept warm for 10-14 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0050] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0051] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1: 0.4-0.6: 0.01-0.02: 450-540: 50-60, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0052] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 90-100°C, kept warm for 20-40 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0053] The nitrate solution is domestic wastewater, industrial wastewater, agricultural wastewater containing nitrate or an aqueous solution prepared using nitrate; the nitrate concentration in the nitrate solution is 0.001-1 g / L.

[0054] The first stirring time is 48 to 60 hours.

[0055] The carbonization treatment is to heat to 390-400°C at a heating rate of 0.5-1°C / min under N2 atmosphere, keep warm for 110-120min, and then heat to 590-600°C at a heating rate of 4.5-5.5°C / min, and keep warm for 110-120min.

[0056] The second stirring time is 10 to 30 minutes.

[0057] The temperature of the second drying is 60-80° C., and the time is 30-60 min. The conditions of the third drying and the fourth drying are the same as those of the second drying.

[0058] The hole scavenger is one of formic acid, ethylene glycol, oxalic acid, isopropanol or ascorbic acid.

[0059] The microwave reaction device is one of a household microwave oven, an industrial microwave oven or a laboratory microwave reactor.

[0060] Example 1

[0061] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0062] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.001:1 to obtain a mixed solution; a hole scavenger accounting for 5 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 2 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1 hour to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 60 minutes under microwave irradiation conditions of 2.45 GHz to obtain ammonia.

[0063] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0064] Step 1: Preparation of ZnFe2O4@C fiber mat

[0065] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:2.4:13 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 60°C and a rotation speed of 800 r / min to obtain an electrospinning solution.

[0066] The electrospinning solution was injected into the syringe of the electrospinning device, and the electrospinning was carried out for 6 hours under the conditions of an applied voltage of 12 kV, an injection speed of 40 μL / min, and a distance of 15 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0067] The ZnFe2O4@C precursor is placed in an oven and dried at 200°C for 4 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0068] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0069] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of 1:2:2.5:18, and stirred for the second time to obtain a suspension III.

[0070] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 200°C, kept warm for 10 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0071] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0072] The ZnFe2O4@C@MoS2 fiber felt, polyvinyl pyrrolidone, PdCl2, ethanol and deionized water are mixed according to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1:0.4:0.01:450:50 to obtain a suspension IV.

[0073] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 90°C, kept warm for 20 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0074] In this embodiment:

[0075] The nitrate solution is an aqueous solution prepared using nitrate; the nitrate concentration in the nitrate solution is 0.1 g / L.

[0076] The first stirring time is 48h.

[0077] The carbonization treatment is to heat to 390°C at a heating rate of 0.5°C / min in a N2 atmosphere, keep the temperature for 110 minutes, and then heat to 590°C at a heating rate of 4.5°C / min, and keep the temperature for 110 minutes.

[0078] The second stirring time is 10 min.

[0079] The second drying temperature is 60° C. and the time is 30 min. The third and fourth drying conditions are the same as the second drying conditions.

[0080] The hole scavenger is formic acid.

[0081] The microwave reaction device is a laboratory microwave reactor.

[0082] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 99.11%, NH4 + The selectivity is 93.92%.

[0083] Example 2

[0084] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0085] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.01:1 to obtain a mixed solution; a hole scavenger accounting for 2 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 1 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1.1 hours to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 30 minutes under a microwave irradiation condition of 0.3 to obtain ammonia.

[0086] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0087] Step 1: Preparation of ZnFe2O4@C fiber mat

[0088] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:2.6:13.4 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 63°C and a rotation speed of 820 r / min to obtain an electrospinning solution.

[0089] The electrospinning solution was injected into the syringe of the electrospinning device, and the spinning was carried out for 6.4 hours under the conditions of an applied voltage of 12.5 kV, an injection speed of 45 μL / min, and a distance between the spinning syringe needle and the collector of 15.5 cm to obtain a ZnFe2O4@C precursor.

[0090] The ZnFe2O4@C precursor is placed in an oven and dried at 205°C for 4.2 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0091] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0092] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of 1:2.2:2.7:20, and stirred for the second time to obtain a suspension III.

[0093] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 205°C, kept warm for 10.5 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0094] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0095] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1:0.43:0.012:459:51, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0096] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 92°C, kept warm for 23 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0097] In this embodiment:

[0098] The nitrate solution is domestic wastewater containing nitrate; the nitrate concentration in the nitrate solution is 0.001 g / L.

[0099] The first stirring time is 50 hours.

[0100] The carbonization treatment is to heat to 391°C at a heating rate of 0.6°C / min in a N2 atmosphere, keep the temperature for 111 minutes, and then heat to 591°C at a heating rate of 4.6°C / min, and keep the temperature for 111 minutes.

[0101] The second stirring time is 13 min.

[0102] The second drying temperature is 63° C. and the time is 33 min. The third and fourth drying conditions are the same as the second drying conditions.

[0103] The hole scavenger is ethylene glycol.

[0104] The microwave reaction device is a laboratory microwave reactor.

[0105] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 43.23%, NH4 + The selectivity is 28.22%.

[0106] Example 3

[0107] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0108] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.05:1 to obtain a mixed solution; a hole scavenger accounting for 3 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 3 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1.2 hours to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 50 minutes under microwave irradiation conditions of 2.45 GHz to obtain ammonia.

[0109] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0110] Step 1: Preparation of ZnFe2O4@C fiber mat

[0111] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:2.8:13.8 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 65°C and a rotation speed of 840 r / min to obtain an electrospinning solution.

[0112] The electrospinning solution was injected into the syringe of the electrospinning device, and the spinning was carried out for 6.8 hours under the conditions of an applied voltage of 13 kV, an injection speed of 50 μL / min, and a distance of 16 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0113] The ZnFe2O4@C precursor is placed in an oven and dried at 210°C for 4.5 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0114] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0115] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of 1:2.4:2.9:22, and stirred for the second time to obtain a suspension III.

[0116] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 210°C, kept warm for 11 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0117] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0118] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1:0.46:0.014:468:52, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0119] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 93°C, kept warm for 25 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0120] In this embodiment:

[0121] The nitrate solution is agricultural wastewater containing nitrate; the nitrate concentration in the nitrate solution is 0.05 g / L.

[0122] The first stirring time was 52 h.

[0123] The carbonization treatment is to heat to 392°C at a heating rate of 0.7°C / min in a N2 atmosphere, keep the temperature for 112 minutes, and then heat to 592°C at a heating rate of 4.7°C / min, and keep the temperature for 112 minutes.

[0124] The second stirring time is 15 min.

[0125] The second drying temperature is 65° C. and the time is 35 min. The third and fourth drying conditions are the same as the second drying conditions.

[0126] The hole scavenger is oxalic acid.

[0127] The microwave reaction device is a household microwave oven.

[0128] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 73.23%, NH4 + The selectivity was 72.25%.

[0129] Example 4

[0130] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0131] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.02:1 to obtain a mixed solution; a hole scavenger accounting for 1 wt% of the mixed solution is added to the mixed solution, the pH of the solution is adjusted to 5 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1.3 hours to obtain a suspension I; the suspension is then placed in a microwave reaction device and reacted for 80 minutes under 5 GHz microwave irradiation conditions to obtain ammonia.

[0132] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0133] Step 1: Preparation of ZnFe2O4@C fiber mat

[0134] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:3:13.9 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 67°C and a rotation speed of 860 r / min to obtain an electrospinning solution.

[0135] The electrospinning solution was injected into the syringe of the electrospinning device, and the electrospinning was carried out for 7 hours under the conditions of an applied voltage of 13.5 kV, an injection speed of 55 μL / min, and a distance of 16.5 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0136] The ZnFe2O4@C precursor is placed in an oven and dried at 215°C for 4.7 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0137] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0138] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of 1:2.6:3:24, and stirred for the second time to obtain a suspension III.

[0139] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 215°C, kept warm for 11.5 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0140] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0141] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1:0.49:0.015:477:53, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0142] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 94°C, kept warm for 30 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0143] In this embodiment:

[0144] The nitrate solution is domestic wastewater containing nitrate; the nitrate concentration in the nitrate solution is 0.01 g / L.

[0145] The first stirring time is 54h.

[0146] The carbonization treatment is to heat to 393°C at a heating rate of 0.8°C / min in a N2 atmosphere, keep the temperature for 113 minutes, and then heat to 593°C at a heating rate of 4.8°C / min, and keep the temperature for 113 minutes.

[0147] The second stirring time is 18 min.

[0148] The second drying temperature is 68° C. and the time is 38 min. The third and fourth drying conditions are the same as the second drying conditions.

[0149] The hole scavenger is isopropyl alcohol.

[0150] The microwave reaction device is a laboratory microwave reactor.

[0151] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 40.62%, NH4 + The selectivity is 29.67%.

[0152] Example 5

[0153] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0154] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.1:1 to obtain a mixed solution; a hole scavenger accounting for 5 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 4 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1.4 hours to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 240 minutes under microwave irradiation conditions of 2.45 GHz to obtain ammonia.

[0155] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0156] Step 1: Preparation of ZnFe2O4@C fiber mat

[0157] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:3.2:14 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 70°C and a rotation speed of 900 r / min to obtain an electrospinning solution.

[0158] The electrospinning solution was injected into the syringe of the electrospinning device, and the spinning was carried out for 7.4 hours under the conditions of an applied voltage of 14 kV, an injection speed of 60 μL / min, and a distance of 17 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0159] The ZnFe2O4@C precursor is placed in an oven and dried at 220°C for 5 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0160] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0161] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of 1:2.8:3.1:25, and stirred for the second time to obtain a suspension III.

[0162] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 220°C, kept warm for 12 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0163] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0164] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1:0.5:0.016:486:54, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0165] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 95°C, kept warm for 30 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0166] In this embodiment:

[0167] The nitrate solution is industrial wastewater containing nitrate; the nitrate concentration in the nitrate solution is 1 g / L.

[0168] The first stirring time was 56 h.

[0169] The carbonization treatment is to heat to 394°C at a heating rate of 0.9°C / min in a N2 atmosphere, keep the temperature for 114 minutes, and then heat to 594°C at a heating rate of 5°C / min, and keep the temperature for 114 minutes.

[0170] The second stirring time is 20 min.

[0171] The second drying temperature is 70° C. and the time is 40 min. The third and fourth drying conditions are the same as the second drying conditions.

[0172] The hole scavenger is ascorbic acid.

[0173] The microwave reaction device is a household microwave oven.

[0174] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 42.68%, NH4 + The selectivity is 44.58%.

[0175] Example 6

[0176] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0177] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.008:1 to obtain a mixed solution; a hole scavenger accounting for 4 wt% of the mass of the mixed solution is added to the mixed solution, the pH of the solution is adjusted to 6 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1.5 hours to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 120 minutes under microwave irradiation conditions of 0.915 GHz to obtain ammonia.

[0178] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0179] Step 1: Preparation of ZnFe2O4@C fiber mat

[0180] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:3.4:14.2 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 72°C and a rotation speed of 920 r / min to obtain an electrospinning solution.

[0181] The electrospinning solution was injected into the syringe of the electrospinning device, and the spinning was carried out for 7.6 hours under the conditions of an applied voltage of 14.5 kV, an injection speed of 65 μL / min, and a distance of 17.5 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0182] The ZnFe2O4@C precursor is placed in an oven and dried at 225°C for 5.4 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0183] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0184] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of 1:3:3.2:26, ​​and stirred for the second time to obtain a suspension III.

[0185] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 225°C, kept warm for 12.5 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0186] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0187] The ZnFe2O4@C@MoS2 fiber felt, polyvinyl pyrrolidone, PdCl2, ethanol and deionized water are mixed according to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt, polyvinyl pyrrolidone, PdCl2, ethanol and deionized water of 1:0.53:0.017:495:55 to obtain a suspension IV.

[0188] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 96°C, kept warm for 33 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0189] In this embodiment:

[0190] The nitrate solution is an aqueous solution prepared using nitrate; the nitrate concentration in the nitrate solution is 0.08 g / L.

[0191] The first stirring time is 58h.

[0192] The carbonization treatment is to heat to 395°C at a heating rate of 0.8°C / min in a N2 atmosphere, keep the temperature for 115 minutes, and then heat to 595°C at a heating rate of 5.1°C / min, and keep the temperature for 115 minutes.

[0193] The second stirring time is 23 min.

[0194] The second drying was carried out at a temperature of 73° C. and for 45 minutes; the third and fourth dryings were carried out under the same conditions as the second drying.

[0195] The hole scavenger is formic acid.

[0196] The microwave reaction device is an industrial microwave oven.

[0197] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 35.61%, NH4 + The selectivity is 43.58%.

[0198] Example 7

[0199] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0200] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.005:1 to obtain a mixed solution; a hole scavenger accounting for 3 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 3 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1.6 hours to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 90 minutes under microwave irradiation conditions of 15 GHz to obtain ammonia.

[0201] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0202] Step 1: Preparation of ZnFe2O4@C fiber mat

[0203] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:3..6:14.5 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 75°C and a rotation speed of 940 r / min to obtain an electrospinning solution.

[0204] The electrospinning solution was injected into the syringe of the electrospinning device, and the spinning was carried out for 7.8 hours under the conditions of an applied voltage of 15 kV, an injection speed of 70 μL / min, and a distance of 18 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0205] The ZnFe2O4@C precursor is placed in an oven and dried at 230°C for 5.6 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0206] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0207] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed according to the mass ratio of the ZnFe2O4@C fiber felt: Na2MoO4·2H2O: thiourea: deionized water of 1:3.4:3.3:27, and stirred for the second time to obtain a suspension III.

[0208] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 230°C, kept warm for 13 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0209] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0210] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1:0.56:0.018:513:57, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0211] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 97°C, kept warm for 35 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0212] In this embodiment:

[0213] The nitrate solution is agricultural wastewater containing nitrate; the nitrate concentration in the nitrate solution is 0.5 g / L.

[0214] The first stirring time was 59 h.

[0215] The carbonization treatment is to heat to 397°C at a heating rate of 0.7°C / min in a N2 atmosphere, keep the temperature for 117 minutes, and then heat to 597°C at a heating rate of 5.2°C / min, and keep the temperature for 117 minutes.

[0216] The second stirring time is 25 min.

[0217] The second drying temperature is 75° C. and the time is 50 min. The third and fourth drying conditions are the same as the second drying conditions.

[0218] The hole scavenger is ethylene glycol.

[0219] The microwave reaction device is a laboratory microwave reactor.

[0220] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate was 87.36%, NH4 + The selectivity is 86.36%.

[0221] Example 8

[0222] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0223] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.02:1 to obtain a mixed solution; a hole scavenger accounting for 2 wt% of the mass of the mixed solution is added to the mixed solution, the pH of the solution is adjusted to 2 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1.8 hours to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 100 minutes under microwave irradiation conditions of 20 GHz to obtain ammonia.

[0224] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0225] Step 1: Preparation of ZnFe2O4@C fiber mat

[0226] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of 1:3.8:14.8 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 78°C and a rotation speed of 980 r / min to obtain an electrospinning solution.

[0227] The electrospinning solution was injected into the syringe of the electrospinning device, and the spinning was carried out for 7.9 hours under the conditions of an applied voltage of 15.5 kV, an injection speed of 75 μL / min, and a distance of 19 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0228] The ZnFe2O4@C precursor is placed in an oven and dried at 235°C for 5.8 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0229] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0230] The ZnFe2O4@C fiber felt, Na2MoO4·2H2O, thiourea and deionized water are mixed according to the mass ratio of the ZnFe2O4@C fiber felt: Na2MoO4·2H2O: thiourea: deionized water of 1:3.6:3.4:29, and stirred for the second time to obtain a suspension III.

[0231] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 235°C, kept warm for 13.5 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0232] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0233] According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1:0.59:0.019:531:59, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV.

[0234] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 99°C, kept warm for 38 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0235] In this embodiment:

[0236] The nitrate solution is domestic wastewater containing nitrate; the nitrate concentration in the nitrate solution is 0.02 g / L.

[0237] The first stirring time is 60h.

[0238] The carbonization treatment is to heat to 399°C at a heating rate of 0.9°C / min in a N2 atmosphere, keep the temperature for 119 minutes, and then heat to 599°C at a heating rate of 5.3°C / min, and keep the temperature for 119 minutes.

[0239] The second stirring time is 28 min.

[0240] The second drying temperature is 78° C. and the time is 55 min. The third drying and fourth drying conditions are the same as the second drying conditions.

[0241] The hole scavenger is isopropyl alcohol.

[0242] The microwave reaction device is a laboratory microwave reactor.

[0243] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 52.35%, NH4 + The selectivity is 45.69%.

[0244] Example 9

[0245] A method for preparing ammonia by microwave catalytic reduction of nitrate. The method for preparing ammonia described in this embodiment is:

[0246] The catalyst is added to the nitrate solution at a mass ratio of catalyst to nitrate solution of 0.01:1 to obtain a mixed solution; a hole scavenger accounting for 1 wt% of the mass of the mixed solution is added to the mixed solution, the pH of the solution is adjusted to 5 with hydrochloric acid, and the solution is placed in a dark room and stirred for 2 hours to obtain a suspension I; and the suspension is placed in a microwave reaction device and reacted for 170 minutes under microwave irradiation conditions of 2.45 GHz to obtain ammonia.

[0247] The catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst, and the preparation method of the catalyst is:

[0248] Step 1: Preparation of ZnFe2O4@C fiber mat

[0249] The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed at a mass ratio of ZnFe2O4 powder: polyacrylonitrile: N,N-dimethylformamide of 1:4:15 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 80°C and a rotation speed of 1000r / min to obtain an electrospinning solution.

[0250] The electrospinning solution was injected into the syringe of the electrospinning device, and the electrospinning was carried out for 8 hours under the conditions of an applied voltage of 16 kV, an injection speed of 80 μL / min, and a distance of 20 cm between the spinning syringe needle and the collector to obtain a ZnFe2O4@C precursor.

[0251] The ZnFe2O4@C precursor is placed in an oven and dried at 240°C for 6 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, it is naturally cooled to room temperature, the product is taken out, and then dried for a second time to obtain a ZnFe2O4@C fiber felt.

[0252] Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt

[0253] The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of 1:4:3.5:30, and stirred for the second time to obtain a suspension III.

[0254] The suspension III was placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor was placed in a hydrothermal oven, heated to 240°C, kept warm for 14 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt.

[0255] Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst

[0256] The ZnFe2O4@C@MoS2 fiber felt, polyvinyl pyrrolidone, PdCl2, ethanol and deionized water are mixed according to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt, polyvinyl pyrrolidone, PdCl2, ethanol and deionized water of 1:0.6:0.02:540:60 to obtain suspension IV.

[0257] The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 100°C, kept warm for 40 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

[0258] In this embodiment:

[0259] The nitrate solution is an aqueous solution prepared using nitrate; the nitrate concentration in the nitrate solution is 0.2 g / L.

[0260] The first stirring time is 60h.

[0261] The carbonization treatment is to heat to 400°C at a heating rate of 1°C / min in a N2 atmosphere, keep the temperature for 120 minutes, and then heat to 600°C at a heating rate of 5.5°C / min, and keep the temperature for 120 minutes.

[0262] The second stirring time is 30 min.

[0263] The second drying temperature is 80° C. and the time is 60 min. The third and fourth drying conditions are the same as the second drying conditions.

[0264] The hole scavenger is oxalic acid.

[0265] The microwave reaction device is an industrial microwave oven.

[0266] The microwave catalytic reduction of nitrate to produce ammonia in this embodiment - The conversion rate is 57.57%, NH4 + The selectivity is 57.36%.

[0267] Compared with the prior art, this embodiment has the following positive effects: 1. The catalyst raw materials used in this embodiment are widely available. Although the precious metal palladium is required in the catalyst raw materials, the loading amount of palladium metal Pd in ​​the catalyst is only 1wt%, so the production cost can be kept low even if the catalyst is prepared on a large scale. In addition, the catalyst is magnetic and can be quickly separated and recovered from the solution by simple magnetic separation. The catalyst has high reusability, so it can reduce production costs and energy consumption. A Pd-ZnFe2O4@C@MoS2 composite microwave catalyst prepared by the present invention is shown in the attached figure. Figure 1 As shown: Figure 1 The X-ray diffraction pattern of the Pd-ZnFe2O4@C@MoS2 composite microwave catalyst prepared in Example 1; Figure 1 It can be seen that the main phase of the catalyst is ZnFe2O4, so the catalyst can be quickly separated and recovered from the solution by simple magnetic separation, and has high reusability.

[0268] 2. The microwave heating method used in this specific embodiment has the characteristics of strong penetration, uniform heating and selective heating. Compared with photocatalysis and electrocatalysis, the unique selective heating of the catalyst by microwaves can ensure that the microwave energy is efficiently used by the catalyst for the catalytic reduction reaction of nitrates, with high energy utilization and low energy consumption, which can significantly reduce production costs.

[0269] 3. The microwave catalytic method used in this specific embodiment utilizes a large number of "hot electrons" excited by the unique "hot spot effect" of microwave irradiation to reduce nitrates. The "hot spot effect" is a high-temperature microscopic quantum dot generated by molecular friction and vibration of the catalyst under microwave irradiation, which can excite "hot electrons" with high energy and catalytic activity. The Pd-ZnFe2O4@C@MoS2 composite microwave catalyst prepared by the present invention is shown in the attached Figure 2 ~Attached Figure 4 As shown: Figure 2 for Figure 1 The scanning electron microscope image of the Pd-ZnFe2O4@C@MoS2 composite microwave catalyst is shown; Figure 3 for Figure 1 Transmission electron microscopy image of the Pd-ZnFe2O4@C@MoS2 composite microwave catalyst shown; Figure 4 for Figure 1 The Pd-ZnFe2O4@C@MoS2 composite microwave catalyst was used to treat 100 mg / L nitrate solution with NO3 - Concentration and NH4 + The concentration changes with the reaction time. Figure 2 It can be seen that the prepared Pd-ZnFe2O4@C@MoS2 composite microwave catalyst has a complex surface structure, which is conducive to the adsorption of NO3 - ;from Figure 3It can be seen that the ZnFe2O4 in the prepared Pd-ZnFe2O4@C@MoS2 composite microwave catalyst is protected inside, so the catalyst can also have high catalytic activity in a complex reaction environment. Figure 4 It can be seen that the NO3 - The conversion rate is 99.11%, NH4 + The selectivity is 93.92%. - The conversion rate is 35.61-99.11%, NH4 + The selectivity is 28.22~93.92%.

[0270] 4. The microwave catalytic method adopted in this specific embodiment only requires mixing the catalyst with the nitrate solution and placing it under microwave irradiation to complete the microwave catalytic reduction of nitrate. The process is simple and the operation is convenient; and there are currently industrial microwave reaction equipment that can support large-scale production.

[0271] Therefore, the specific implementation has the characteristics of simple operation, low cost, low energy consumption, reusable catalyst and easy large-scale production. The method of preparing ammonia by microwave catalytic reduction of nitrate has high ammonia production efficiency and high ammonia selectivity.

Claims

1. A method for preparing ammonia by microwave catalytic reduction of nitrates, wherein the method is characterized in that: according to a mass ratio of catalyst to nitrate solution of 0.001 to 0.1:1, the catalyst is added to the nitrate solution to obtain a mixed solution; then a hole scavenger accounting for 1 to 5 wt% of the mass of the mixed solution is added to the mixed solution, the pH value of the solution is adjusted to 1 to 6 with hydrochloric acid, and the solution is placed in a dark room and stirred for 1 to 2 hours to obtain a suspension I; then the suspension is placed in a microwave reaction device and reacted for 30 to 240 minutes under microwave irradiation conditions of 0.3 to 20 GHz to obtain ammonia; the catalyst is a Pd-ZnFe2O4@C@MoS2 composite catalyst.

2. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The preparation method of the catalyst is: Step 1: Preparation of ZnFe2O4@C fiber mat The ZnFe2O4 powder, the polyacrylonitrile and the N,N-dimethylformamide are mixed in a mass ratio of ZnFe2O4 powder: polyacrylonitrile: N,N-dimethylformamide of 1:2.4-4:13-15 to obtain a suspension II; the suspension II is placed on a magnetic stirrer and stirred for the first time at a temperature of 60-80°C and a rotation speed of 800-1000 r / min to obtain an electrospinning solution; The electrospinning solution is injected into the syringe of the electrospinning device, and the electrospinning is performed for 6 to 8 hours under the conditions of an applied voltage of 12 to 16 kV, an injection speed of 40 to 80 μL / min, and a distance between the spinning syringe needle and the collector of 15 to 20 cm to obtain a ZnFe2O4@C precursor; The ZnFe2O4@C precursor is placed in an oven and dried at 200-240°C for 4-6 hours to obtain a spinning product; the spinning product is placed in a tubular furnace for carbonization treatment; after the carbonization treatment is completed, the product is naturally cooled to room temperature, and then dried for a second time to obtain a ZnFe2O4@C fiber felt; Step 2: Preparation of ZnFe2O4@C@MoS2 fiber felt The ZnFe2O4@C fiber felt, the Na2MoO4·2H2O, the thiourea and the deionized water are mixed in a mass ratio of the ZnFe2O4@C fiber felt: Na2MoO4·2H2O: thiourea: deionized water of 1:2-4:2.5-3.5:18-30, and stirred for a second time to obtain a suspension III; The suspension III is placed in a polytetrafluoroethylene hydrothermal reactor, and then the polytetrafluoroethylene hydrothermal reactor is placed in a hydrothermal oven, heated to 200-240° C., kept warm for 10-14 hours, naturally cooled to room temperature, filtered, and dried for the third time to obtain ZnFe2O4@C@MoS2 fiber felt; Step 3: Preparation of Pd-ZnFe2O4@C@MoS2 composite microwave catalyst According to the mass ratio of the ZnFe2O4@C@MoS2 fiber felt: polyvinyl pyrrolidone: PdCl2: ethanol: deionized water of 1: 0.4-0.6: 0.01-0.02: 450-540: 50-60, the ZnFe2O4@C@MoS2 fiber felt, the polyvinyl pyrrolidone, the PdCl2, the ethanol and the deionized water are mixed to obtain a suspension IV; The suspension IV was placed in a water bath heating pot, connected to an external condenser reflux tube, heated to 90-100°C, kept warm for 20-40 minutes, naturally cooled to room temperature, the product was taken out, and dried for the fourth time to obtain a Pd-ZnFe2O4@C@MoS2 composite microwave catalyst.

3. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The nitrate solution is domestic wastewater, industrial wastewater, agricultural wastewater containing nitrate or an aqueous solution prepared using nitrate; the nitrate concentration in the nitrate solution is 0.001-1 g / L.

4. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The first stirring time is 48 to 60 hours.

5. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The carbonization treatment is to heat to 390-400°C at a heating rate of 0.5-1°C / min under N2 atmosphere, keep warm for 110-120min, and then heat to 590-600°C at a heating rate of 4.5-5.5°C / min, and keep warm for 110-120min.

6. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The second stirring time is 10 to 30 minutes.

7. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The temperature of the second drying is 60-80° C. and the time is 30-60 min. The conditions of the third drying and the fourth drying are the same as those of the second drying.

8. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The hole scavenger is one of formic acid, ethylene glycol, oxalic acid, isopropanol or ascorbic acid.

9. The method for preparing ammonia by microwave catalytic reduction of nitrates according to claim 1, characterized in that: The microwave reaction device is one of a household microwave oven, an industrial microwave oven or a laboratory microwave reactor.

Citation Information

Patent Citations

  • Preparation method of porous carbon nitride-ferrite composite catalyst with nitrogen / oxygen dual defect structure and light nitrogen fixation application

    CN113976155A

  • In-situ growth copper-containing photocatalyst, preparation method and application of in-situ growth copper-containing photocatalyst in nitrate reduction synthesis of ammonia

    CN115920887A

  • Water treatment method for controllably converting nitrate into ammonia or nitrogen on same photocatalyst

    CN116835713A

  • Iron monatomic doped 3D defect carbon nitride electrode and preparation method and application thereof

    CN118028893A